The investigation of antioxidant and anti-inflammatory potentials of apitherapeutic agents on heart tissues in nitric oxide synthase inhibited rats via N?-nitro-L-arginine methyl ester - Ozdemir, Betul; Gulhan, Mehmet Fuat; Sahna, Engin; Selamoglu, Zeliha (Taylor & Francis Inc, 2021)
Background High blood pressure effects heart and vessels. Development of pathogenesis is the result of oxidative stress. We aimed to investigate the antioxidant effects of propolis, caffeic acid phenethyl ester (CAPE), and pollen on the hearts of rats which chronic nitric oxide synthase (NOS) inhibited through N omega-nitro-L-arginine methyl ester (L-NAME). Paraoxonase 1 (PON1), total antioxidant status (TAS), total oxidant status (TOS), oxidative stress index (OSI), asymmetric dimethylarginine (ADMA), and nuclear factor-kappa B (NF-kappa B) were analyzed on the heart. Material and Methods Sprague-Dawley rats were divided five groups of seven rats in every group; Group I: Control, Group II: L-NAME, Group III: L-NAME+propolis, Group IV: L-NAME+CAPE and Group V: L-NAME+pollen. L-NAME become dissolved in regular saline (0.9% NaCl w/v). The ethanolic extract of propolis (200 mg/kg/days, gavage), pollen (100 mg/kg/days, by gavage), CAPE (50 mu M/kg/days, intraperitoneally), and the NOS inhibitor L-NAME (40 mg/kg, intraperitoneally) had been administered. Results Blood pressure (BP) of rats treated with propolis, CAP,E and pollen statistically significant decreased. Decreasing in BP of the rats of pollen group was more than CAPE and propolis groups (P< .05). PON1 and TAS levels decreased in L-NAME-treated groups (P< .05), but ranges have been better in propolis, CAPE and pollen groups. TOS, ADMA and NF-kappa B levels increased (P< .05) in L-NAME group; however, these parameters were lower (P< .05) in propolis and CAPE groups (P< .05). Conclusions Vasorelaxant properties and free radical scavenging actions of propolis, CAPE, and pollen may reduce the oxidative stress and blood pressure in the rats chronic NOS inhibited through L-NAME.
Keywords: Anti-inflammatory effect; antioxidant; apitheraphy; heart; hypertension; oxidative stress; rat